A Stretchable Pillararene-Containing Supramolecular Polymeric Material with Self-Healing Property - Meng Zhao; Changjun Li; Xiaotao Shan; Huijing Han; Qiuhua Zhao; Meiran Xie; Jianzhuang Chen; Xiaojuan Liao (Molecules, 2021)
Constructing polymeric materials with stretchable and self-healing properties arise increasing interest in the field of tissue engineering, wearable electronics and soft actuators. Herein, a new type of supramolecular cross-linker was constructed through host-guest interaction between pillar[5]arene functionalized acrylate and pyridinium functionalized acrylate, which could form supramolecular polymeric material via photo-polymerization of n-butyl acrylate (BA). Such material exhibited excellent tensile properties, with maximum tensile strength of 3.4 MPa and strain of 3000%, respectively. Moreover, this material can effectively dissipate energy with the energy absorption efficiency of 93%, which could be applied in the field of energy absorbing materials. In addition, the material showed self-healing property after cut and responded to competitive guest.